ROLE OF DIGITAL ECONOMY IN ECONOMIC DEVELOPMENT (International journal of artificial intelligence, 2025)
The article highlights the role and overall importance of the digital economy in modern economic development. The impact of digital technologies on production, service delivery, public administration, and social life is analyzed. Online commerce, electronic payments, digital banking services, automation, and artificial intelligence are identified as key factors enhancing economic efficiency. Along with the positive aspects of the digital economy, issues related to digital inclusion, cybersecurity, and the labor market are also addressed. Overall, the article substantiates that the digital economy is a crucial factor in ensuring economic growth, transparency, innovation, and competitiveness.